Recruiting for Caregiver Education Research: Perspectives of Caregivers of People with Multiple Sclerosis - Preissner, Katharine (The Consortium of Multiple Sclerosis Centers, 2012)
Caregiver education programs can support participants in a role that is often challenging. Research is needed to determine the effectiveness of these programs; however, recruitment for such studies can be difficult. The objectives of this study were to explore 1) how multiple sclerosis (MS) caregivers respond to recruitment materials for a research study evaluating a caregiver education program, including aspects of the materials that encourage or discourage their interest in participation; and 2) what recommendations MS caregivers have for improving study recruitment advertising. Qualitative interviews were conducted with seven MS caregivers. Participants were asked about their reactions to advertisements for a pilot study intended to evaluate an MS caregiver education program. Participants were also asked to reflect on factors that would influence their decision to participate in the program and to provide suggestions to improve recruitment materials. Data were analyzed using a constant-comparative approach. Study findings indicated that the language and visual design of the advertisements influenced the participants' initial responses. Some caregivers first responded to the fact that the program was part of a research study, and these caregivers had overall negative responses to the advertising, such as concern that the program was being “tested.” Other caregivers first considered the personal relevance of the program. These caregivers had neutral-to-positive responses to the flyers and weighed the relevance of the program against the research and logistical aspects. Participants provided recommendations to improve the recruitment materials. While recruiting for caregiver education research can be challenging, piloting recruitment materials and using a variety of advertising options may improve response.